(untitled) (Palimpsesto, 2022)
This article review the concept of landscape from Geography studies and Art history, amplifying some relevant findings of research titled “Guatavita: el paisaje bajo las aguas del progreso y el resurgimiento del habitar” (Guatavita: the landscape under the waters of progress and the resurgence of inhabiting). The text presents reflections around the forms that the concept of landscape could be assumed to inquire into social realities, related to the ways people appropriate the inhabited space through their vital experiences.